Hyperbranched polymer based fluorescent probes for ppt level nerve agent simulant vapor detection. Issue 11 (1st March 2017) - Jiang, Haibo; Wu, Pengcheng; Zhang, Yu; Jiao, Zinuo; Xu, Wei; Zhang, Xiangtao; Fu, Yanyan; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract : A terpyridine end capped hyperbranched polymer for the sensitive detection of sarin mimic diethyl chlorophosphate. Abstract : Sarin is a nerve agent that is usually used in terrorist attacks. Diethyl chlorophosphate (DCP) has a similar reactivity to sarin, but lacks high toxicity, so DCP is a good model compound for sarin detection. Terpyridine is a common functional unit used in coordination compounds, but not used in toxic gas detection. In this contribution, multiple terpyridine units were introduced into the periphery of hyperbranched conjugated polymers with pyrene as the core and fluorene as connecting units for highly efficient DCP detection, which utilized the excellent properties of hyperbranched polymers including high functional group density, efficient energy transfer from the core to the periphery units, etc. As compared with linear small molecular probes, terpyridine end capped hyperbranched polymers showed much better photostability and sensitivity to DCP vapor. The fluorescence was almost completely quenched under saturated DCP vapor within 3 s and the emission peak red-shifted from 468 nm to 554 nm. A concentration of 65 ppt DCP with a quenching efficiency of 3.6% could be detected, which is far better than the results estimated by others. Therefore, multiple terpyridine end capped hyperbranched polymers are a very promising probe for nerve agent detection whatever in the sensitivity or response rate.